Early and Middle Woodland Landscapes of the Southeast - Henry, Edward R.; Wright, Alice P. (Book collections on Project MUSE., 2013)
The Early and Middle Woodland periods (1000 BCE-500 CE) were remarkable for their level of culture contact and interaction in pre-Columbian North America. This volume, featuring case studies from Georgia, Florida, North Carolina, Mississippi, Kentucky, Alabama, and Tennessee, sheds light on the various approaches to the study of the dynamic and complex social landscapes of these eras. Essays by well-known and up-and-coming scholars incorporate empirical data with social organizational concepts such as ritual, cultural, and social places, highlighting the variability and common themes in the relationships between people, landscapes, and the built environment that characterize this period of North American native life.